Learning together: responding to change and complexity to improve community forests in the Philippines - Hartanto, H.; Lorenzo, M.C.B.; Valmores, C.; Arda-Minas, L.; Burton, L.; Prabhu, Ravi (Center for International Forestry Research, 2003)
Community forestry in the Philippines has gone through a long process of change over the last thirty years. It reached a high level of achievement with the creation of a comprehensive and integrated programme called Community-Based Forest Management (CGFM) in 1995. In this programme, local people are recognised as partners in the management and protection of the country's forests and forest resorces. However, the government, and other local stakeholders still face problems in implementing the programme effectivelly. This book introduces a learning-based approach called Adaptive Collaborative Management (ACM) as a potential way to deal with the challenges of CBFM. It draws on the experience and lessons learnt from CIFOR collaborative research in two CBFM sites in the Philippines. It also describes how local people and stakeholders in the two sites applied the ACM approach and process to address their local problems, the outcomes of their efforts, and the challenges that remain.